The Development of Comics as Social Studies Learning Media in International Trade Materials for Class VIII SMP - Putra Bernadus Banilo; Yulita Pujiharti (Economics and Education Journal (Ecoducation), 2021)
This study aims to develop comics as a medium of learning with the subject matter of international trade for class VIII SMP. The approach used is research and development (R & D). This research method is mixed methods design. The subjects in this study were students of SMP 'Aisyiyah Muhammadiyah 3 Malang. Data collection techniques using questionnaires and observation. The comic developed refers to the stages of development by Thiagarajan (1974) namely the development of a modified 4D model according to research needs. The results of the study show that thelearning media is comic very feasible to be applied in social studies learning with the subject of international trade for class VIII SMP. Quantitatively, the assessment of the material expert is (3.27) with a very valid category. The expert assessment is based on the suitability of the curriculum, the truth of the content and the method of presenting the material is included in the very valid category), and the media expert's assessment obtained a score of (3.20) with a very valid category. The media expert's assessment is based on considerations of visual design, language in the media and the quality of graphics, the score (3.20) is in the very valid category. Meanwhile, the student response sheets that were distributed to measure the level of attractiveness ofmedia comics received a response of 84.5% with a very good category. However, the pilot phase in this study could not be carried out as a whole, this was caused by the constraints experienced by the researchers. The percentage level of attractiveness of the media obtained from the student response sheets shows that the learning media for comics is in a very good category, which means that the learning media for comics is effectively used in the subject matter of international trade for class VIII SMP. Qualitatively,media comics as learning media on the subject of international trade are able to attract students' attention to study, facilitate student learning, and assist students in relating international trade material to everyday events.